Fusing a Carbohydrate-Binding Module into the Aspergillus usamii β-Mannanase to Improve Its Thermostability and Cellulose-Binding Capacity by In Silico Design - Tang, Cun-Duo; Li, Jian-Fang; Wei, Xi-Huan; Min, Rou; Gao, Shu-Juan; Wang, Jun-Qing; Yin, Xin; Wu, Min-Chen (PLOS ONE, 2013)
The AuMan5A, an acidophilic glycoside hydrolase (GH) family 5 β-mannanase derived from Aspergillus usamii YL-01-78, consists of an only catalytic domain (CD). To perfect enzymatic properties of the AuMan5A, a family 1 carbohydrate-binding module (CBM) of the Trichoderma reesei cellobiohydrolase I (TrCBH I), having the lowest binding free energy with cellobiose, was selected by in silico design, and fused into its C-terminus forming a fusion β-mannanase, designated as AuMan5A-CBM. Then, its encoding gene, Auman5A-cbm, was constructed as it was designed theoretically, and expressed in Pichia pastoris GS115. SDS-PAGE analysis displayed that both recombinant AuMan5A-CBM (reAuMan5A-CBM) and AuMan5A (reAuMan5A) were secreted into the cultured media with apparent molecular masses of 57.3 and 49.8 kDa, respectively. The temperature optimum of the reAuMan5A-CBM was 75°C, being 5°C higher than that of the reAuMan5A. They were stable at temperatures of 68 and 60°C, respectively. Compared with reAuMan5A, the reAuMan5A-CBM showed an obvious decrease in Km and a slight alteration in Vmax. In addition, the fusion of a CBM of the TrCBH I into the AuMan5A contributed to its cellulose-binding capacity.